Improve the physical and chemical properties of camel’s hair fiber in Afif province - Mokhtar, Leila Mahmoud; Moussa, Enas Ibrahim (Journal of natural sciences, life and applied sciences, 2019)
The study aimed to draw attention to the camel’s hair available in Afif province and to give information about their physical and chemical properties, and improve their properties. The researchers’ collected 50 samples of camel’s hair, analyze, and then add improvement material. The study concluded that the Afif Province camel’s hair have properties that can converted into textile materials. The softness are from 24.5 to 29 μ, (B and C1) according to the classification of the German system GER, and between 58 S And 60 S according to the classification of (USA, AUS, GRB). The thickness between 5.3 - 12 cn/ tex. The length between (3.8 - 25.5 cm), and the colors of camels hair (Brown, light brown, light creamy, dark creamy). The chemical properties were similar to the global chemical properties of wool, Absorption of moisture from 0.10% to 0.26%, the protein content from 52% to 95%, and its capable temperature to 140 °C without occur softness or fusion, and after 140 degree centigrade the decomposition occurs. Characteristics of the camel’s hair can improve by adding some chemicals, such as acetic acid to improve the softness without affecting the durability, or by mixed with other fiber.